Future scenarios based on a CA-Markov land use and land cover simulation model for a tropical humid basin in the Cerrado/Atlantic forest ecotone of Brazil. (February 2021) - Cunha, Elias Rodrigues da; Santos, Celso Augusto Guimarães; Silva, Richarde Marques da; Bacani, Vitor Matheus; Pott, Arnildo
Highlights: Recently, the advancement of agriculture in Brazil has caused very serious problems, such as deforestation. Future impacts of the advancement of agriculture in the Cerrado/Atlantic forest ecotone in 2033, 2050, 2080 and 2100. The future LULC scenarios were created with a cellular automata-Markov forecast model. The results indicated the advancement of crop agriculture and decreases in important areas. The results can help the effectiveness of public policies to reduce deforestation in the area. Abstract: Recently, the advancement of agriculture in Brazil has caused very serious problems, such as deforestation and an increase in the amount of pesticides and suspended sediment that have negatively impacted the environment, especially in the Prata River basin, which is located in the Serra da Bodoquena region, Brazil. Thus, the objective of this study was to analyze the future changes in land use and land cover of the advancement of agriculture in the native vegetation areas of the Cerrado/Atlantic forest ecotone in the Prata River basin in 2033, 2050, 2080 and 2100. To map the future land use and land cover (LULC) in the study area, an object-based classification approach was used on Landsat satellite imagery from 1986, 1999, 2007 and 2016. The future LULC scenarios were created with a cellular automata-Markov forecast model. The simulation results of the LULC changes were considered satisfactory, as evidenced by the values obtained from the kappa for agreement (κstandard ) = 0.73, kappa for no information (κno ) = 0.79 and kappa for grid-cell level location (κlocation ) = 0.85 indices. The modeled future scenarios of LULC indicated the advancement of crop agriculture and decreases in wetlands ( banhado ), savannahs, riparian forests, seasonal semideciduous forests and wet grasslands, which can be considered a warning about the loss of biodiversity of fauna and flora in the Serra da Bodoquena National Park, mainly in the Prata River basin.